Health gains, costs and cost‐effectiveness of a population‐based screening programme for abdominal aortic aneurysms. Issue 8 (22nd May 2019) - Nair, N.; Kvizhinadze, G.; Jones, G. T.; Rush, R.; Khashram, M.; Roake, J.; Blakely, A.
Abstract : Background: Abdominal aortic aneurysm (AAA) rupture carries a high fatality rate. AAAs can be detected before rupture by abdominal ultrasound imaging, allowing elective repair. Population‐based screening for AAA in older men reduces AAA‐related mortality by about 40 per cent. The UK began an AAA screening programme offering one‐off scans to men aged 65 years in 2009. Sweden has a similar programme. Currently, there is no AAA screening programme in New Zealand. This cost–utility analysis aimed to assess the cost‐effectiveness of a UK‐style screening programme in the New Zealand setting. Methods: The analysis compared a formal AAA screening programme (one‐off abdominal ultrasound imaging for about 20 000 men aged 65 years in 2011) with no systematic screening. A Markov macrosimulation model was adapted to estimate the health gains (in quality‐adjusted life‐years, QALYs), health system costs and cost‐effectiveness in New Zealand. A health system perspective and lifetime horizon was adopted. Results: With New Zealand‐specific inputs, the adapted model produced an estimate of about NZ 15 300 (€7746) per QALY gained, with a 95 per cent uncertainty interval (UI) of NZ 8700 to 31 000 (€4405 to 15 694) per QALY gained. Health gains were estimated at 117 (95 per cent UI 53 to 212) QALYs. Health system costs were NZ 1·68 million (€850 535), with a 95 per cent UI of NZ 820 200 to 3·24 million (€415 243 to €1·65 million). Conclusion: Using New Zealand's gross domestic product per capita (about NZ 45 000 or €22 100) as a cost‐effectiveness threshold, a UK‐style AAA screening programme would be cost‐effective in New Zealand. Abstract : Currently, there is no abdominal aortic aneurysm (AAA) screening programme in New Zealand. This cost–utility analysis aimed to assess the cost‐effectiveness of a UK‐style screening programme in the New Zealand setting. With New Zealand‐specific inputs, the adapted model produced an estimate of about NZ 15 300 per QALY gained (€7746), with a 95 per cent uncertainty interval of NZ 8700 to 31 000 (€4405 to 15 694). Using New Zealand's gross domestic product per capita (about NZ 45 000 or £22 100) as a cost‐effectiveness threshold, a UK‐style AAA screening programme would be cost‐effective in New Zealand. Cost‐effective in New Zealand too